Comparative Analysis of National and Regional Models of the Silver Economy in the European Union - Andrzej Klimczuk (International Journal of Ageing and Later Life, 2016)
The approach to analysing population ageing and its impacts on the economy has evolved in recent years. There is increasing interest in the development and use of products and services related to gerontechnology as well as other social innovations that may be considered as central parts of the “silver economy.” However, the concept of silver economy is still being formed and requires detailed research. This article proposes a typology of models of the silver economy in the European Union (EU) at the national and regional levels. This typology was created by comparing the Active Ageing Index to the typology of varieties and cultures of capitalism and typology of the welfare states. Practical recommendations for institutions of the EU and directions for further research are discussed.
Keywords: J14; O57; R19; 330; Active ageing index; regional development; silver economy; varieties/cultures of capitalism; welfare state